2022
DOI: 10.3389/fonc.2022.783197
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inflammatory Markers on the Survival of Advanced Gastric Cancer Patients Who Underwent Anti-Programmed Death 1 Therapy

Abstract: PurposeThis clinical study sought to determine whether the levels of inflammatory markers predicted the survival of advanced gastric cancer (AGC) patients who underwent anti-programmed death 1 (PD-1) therapy.MethodsUsing AGC patient plasma samples and baseline characteristics, we investigated the specific value of inflammatory markers in AGC from a clinical perspective in immunotherapy.ResultsOne hundred and six patients with AGC who underwent anti-PD-1 therapy were enrolled in this study between 20 July 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Serum inflammatory markers have the advantages of being convenient, repeatable and inexpensive in comparison to current biomarkers like PD-L1 and MSI. Thus, their predictive or prognostic value has been systematically analyzed in a variety of cancers such as NSCLC ( 26 ), renal cancer ( 27 ), as well as gastric cancer ( 28 ). Similar studies were also performed in EC patients treated with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Serum inflammatory markers have the advantages of being convenient, repeatable and inexpensive in comparison to current biomarkers like PD-L1 and MSI. Thus, their predictive or prognostic value has been systematically analyzed in a variety of cancers such as NSCLC ( 26 ), renal cancer ( 27 ), as well as gastric cancer ( 28 ). Similar studies were also performed in EC patients treated with immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence has shown that inflammatory markers can predict short-term efficacy of immunotherapy in advanced gastric cancer patients. A study comprising 37 patients with advanced gastric cancer treated with first-line immunotherapy showed that PLR was an independent predictor of the OS but not the PFS ( 22 ). The baseline and early changes of MLR have been shown to influence survival outcomes in advanced gastric cancer on different lines ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, most studies on inflammatory factors in gastric cancer treated with immunotherapy are based on single cohorts. Little focus has been paid to the identification of the function of MLR in patients using real-world cohorts ( 22 ). Based on results obtained from the clinical trial cohort, we concluded that NLR was an independent prognostic factor, a finding that was validated in the real-world cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Asher et al (30) reported that PLR was an independent prognostic marker in patients with ovarian cancer and revealed that higher PLR values were associated with poorer prognosis. Qu et al (31) demonstrated that NLR and PLR could be used as predictors of near-term outcome in patients with advanced gastric cancer receiving immunotherapy. In addition, Song et al (32) evaluated 389 patients receiving concurrent radiotherapy, and revealed that higher NLR and PLR values were associated associations were not observed in multivariate analysis; this finding is consistent with those of previous studies (30,32).…”
Section: Discussionmentioning
confidence: 99%